The Impact of Perception toward the Built Environment in Airport Access Mode Choice Using Hybrid Choice Modeling - Mahdi Yazdanpanah; Mansour Hadji Hosseinlou (Journal of Advanced Transportation)
Built environment (BE), as an objective variable, plays a substantial role in urban residents’ behavior. However, the perception toward a BE, as a subjective variable, varies among people. To identify the role of perception toward BE, we used a stated preference (SP) survey conducted in January–February 2015 at the Imam Khomeini International Airport (IKIA), Tehran, Iran. The data was drawn from 641 individuals; 359 of them were residents of Tehran. For the estimation of the model, a hybrid discrete choice model was used to capture the latent variable, in addition to mode attributes and trip conditions, with 1795 SP observations. Psychometric questions concerned the perception of ease in access to main streets or highways and good traffic conditions within their residential areas. The results showed that the latent variable (positive perception toward built environment or PBE) had a significant positive effect on people’s willingness to park at the airport. Moreover, the gender, age, marital status, level of education, experience living in a foreign country, and income level also influenced the formation of perception toward the BE and airport transportation mode choice.